LANDSCAPES AND ARKHYZ RECREATIONAL VALUE - Viktor Alexandrovich Shalnev; Ekaterina Aleksandrovna Lyashenko (Вестник Северо-Кавказского федерального университета, 2022)
The present state of Arkhyz landscapes, variety of recreational resources in the organization of land- scape and ecological tourism. Special attention climatic resources and their uniqueness when compared with other mountain climatic resort.